STUDENTS’ PERCEPTION OF USING BRITISH COUNCIL LEARN ENGLISH FOR INCREASING VOCABULARY ACQUISITION - Aisyah Hafizha Ibrahim Sihombing; Siti Ismahani (SOSIOEDUKASI, 2025)
Building vocabulary is crucial to improving students' language skills, yet many EFL students find it difficult to pick up a wide enough vocabulary using conventional teaching techniques. This study aims to investigate how students view the British Council Learn English platform as a digital resource for vocabulary development. Fifteen Junior high school students who had been active platform users for at least a month participated in semi-structured interviews as part of a qualitative descriptive technique to gather data. Key themes were identified through the use of thematic analysis. According to the results, students thought the platform was helpful, efficient, and interesting for vocabulary development, especially because of its interactive content, contextualized learning resources, and audiovisual elements. Nevertheless, many drawbacks were identified, including the absence of speaking practice and the repetitive nature of the activity formats. These findings imply that although the platform greatly facilitates vocabulary acquisition, more work is required to meet students' more extensive language requirements. To optimize the platform's pedagogical potential and student happiness, educators and developers are advised to incorporate elements that encourage speaking practice, collaborative learning, and content variety. To optimize the platform's pedagogical potential and student happiness, educators and developers are advised to incorporate elements that encourage speaking practice, collaborative learning, and content variety